Integrated Learning Model in Improvement Learning Quality : The Qualitative study at SMP Negeri Aceh Besar - Cut Nya’dhin,; Fuady,; Basri,; Anwar,; Abubakar, (Jurnal Serambi Ilmu, 2024)
This research aims to determine integrated learning policies and programs in improving the quality of student learning at SMPN 3 Ingin Jaya, The research method used is a qualitative method, Metode dalam penelitian yang digunakan adalah metode kualitatif, research procedures that use descriptive data in the form of written or spoken words from people and actors observed through observations and interviews. The research subjects were the principal, 2 teachers and 3 3rd grade students. The research results show: 1) policies implemented in schools SMP 3 Ingin Jaya Where every student is obliged to memorize Joz 30 and have noble character, The learning model used at SMPN 3 Ingin Jaya is for tahfiz learning using the Talqin model, Meanwhile, for early learning, the problem best learning model is used.